2011
DOI: 10.12659/msm.881325
|View full text |Cite
|
Sign up to set email alerts
|

Elevated resistin opposed to adiponectin or angiogenin plasma levels as a strong, independent predictive factor for the occurrence of major adverse cardiac and cerebrovascular events in patients with stable multivessel coronary artery disease over 1-year follow-up

Abstract: SummaryBackgroundAdipokines such as adiponectin and resistin, as well as angiogenin, may be associated with inflammation and atherosclerosis. The relationship between their levels and prognosis in high risk patients is, however, still unclear. The aim of this study was to evaluate the prognostic value of these adipokines in patients with stable multivessel coronary artery disease (MCAD).Material/MethodsThe study group comprised 107 MCAD patients (74% males, mean age 63±8 years). Adiponectin, resistin and angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…However, Kreçki et al, revealed the presence of a positive correlation between serum resistin in human subjects and the risk level for the development of CVDs (53). McManus et al showed that resistin concentrations were inversely related to LVFS (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kreçki et al, revealed the presence of a positive correlation between serum resistin in human subjects and the risk level for the development of CVDs (53). McManus et al showed that resistin concentrations were inversely related to LVFS (54).…”
Section: Discussionmentioning
confidence: 99%
“…Serum resistin levels showed a stepwise increase with the number of >50% stenosed coronary vessels in patients with stable CAD ). Furthermore, resistin was an independent predictor of major adverse cardiovascular events, including cardiovascular death and myocardial infarction and restenosis in patients undergoing percutaneous coronary intervention Krecki et al, 2011;Momiyama et al, 2011). In addition to these association between resistin and stable coronary artery diseases, elevated plasma resistin level was suggested to predict the development of myocardial infarction in a case-cohort study of 26,490 middle-aged subjects from the European Investigation into Cancer and Nutrition-Potsdam Study without history of MI or stroke with a relative risk of 2.09, adjusted for CRP (Weikert et al, 2008).…”
Section: Human Resistin In Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%
“…In patients with stable multivessel coronary artery disease, Krecki et al (42) found that elevated plasma resistin was a strong, independent predictive factor for the occurrence of major adverse cardiac and cerebrovascular events. Although in some studies plasma levels of resistin were correlated with mortality (43)(44)(45), in most prospective clinical studies resistin fails to appear as an independent risk factor for cardiovascular events and mortality (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%